Estimation of Bimodal Urban Link Travel Time Distribution and Its Applications in Traffic Analysis. (7th September 2015) - Ji, Yuxiong; Jiang, Shengchuan; Du, Yuchuan; Zhang, H. Michael
Abstract : Vehicles travelling on urban streets are heavily influenced by traffic signal controls, pedestrian crossings, and conflicting traffic from cross streets, which would result in bimodal travel time distributions, with one mode corresponding to travels without delays and the other travels with delays. A hierarchical Bayesian bimodal travel time model is proposed to capture the interrupted nature of urban traffic flows. The travel time distributions obtained from the proposed model are then considered to analyze traffic operations and estimate travel time distribution in real time. The advantage of the proposed bimodal model is demonstrated using empirical data, and the results are encouraging.